The literary death and legal death in Fabla salvaje - Rodríguez Chávez, Iván (2023)
This article analyses the short novel Fabla salvaje, published in 1923, in which its author, César Vallejo, develops the story of Balta Espinar, a young farmer married to Adelaida, who becomes captive of a superstition of tragedy unleashed by the accidental breakage of a mirror, an event that affects his mental health and generates a delirium of persecution of an «invisible being» and non-existent, like his own double; but this will plunge him into a depressive state of mind, personal insecurity, distrust and fatalism, which modifies his behaviour towards his wife, with whom he becomes sullen, with unfounded jealousy, causing her suffering and without taking into account the pregnancy of their first child. This superstition, which is reinforced by the song of a hen and two owls, has changed Balta Espinar’s attitude towards the world and life, leading him to death. The present study will be carried out from the perspective of a literary-legal interpretation, especially of the figures of freedom and death.